Influence of solid oxide fuel cell on power system transient stability. Issue 16 (6th December 2018) - Liu, Jun; Su, Can; Wang, Chao; Zhu, Longyang; He, Jian
Abstract : Due to its modular, efficient and non‐polluting characteristics, solid oxide fuel cell (SOFC) is promising to be widely utilised in the area of distributed generation. Previous studies mainly focused on dynamic modelling of SOFC to analyse its load following behaviour, however, the influence of SOFC on power system transient stability is not yet clear and needs further discussion. In this study, a system‐level electromechanical transient mathematical model for SOFC is proposed, based on the circuit structure of SOFC, DC/DC step‐up converter and DC/AC converter. Then, a double closed‐loop control scheme is designed for the control of SOFC. Finally, the effect of SOFC on the power system's transient stability is discussed through simulations based on IEEE 3‐machine 9‐bus standard system. Results show that, under real and reactive power coordinated control strategy, cell current can be adjusted. Therefore, the output power of SOFC can be modulated to help with voltage recovery and power angle stability. The authors' work reveals the feasibility of using SOFC to enhance power system transient stability.